BUILDING STUDENTS’ CHARACTER THROUGH WRITING DESCRIPTIVE TEXT - Rini Anita (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2014)
Nowadays, some behavioral problems like cheating in schools, bullying, pervasive youth violence and other problems are well documented. These misbehaviors have made the needs of character building among students are obviously required in any level of education. It is therefore important for teachers to instill their students with noble characters like honesty, cooperative, responsibility, discipline, creativity, and so forth. These characters can be built through writing activities. Hence descriptive text and the activities of writing processes can be an alternative way to engrave their noble characters. This paper attempts to describe character education, character and good characters; explores on kinds of good characters that can be implied in writing descriptive text; and how descriptive text can build students’ good character. Keywords: Character Education, Good Characters, Descriptive Text, Behavioral problems